PERILAKU KONSUMTIF : LITERASI KEUANGAN, PENGETAHUAN EKONOMI DAN MODERNITAS INDIVIDU - Wanda Nuara Ciptasari; Endah Andayani; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2017)
This study aims to examine 1) knowing the effect of financial literacy, economic knowledge and individual modernity on consumptive behavior, 2) knowing the effect of financial literacy on consumptive behavior 3) knowing the effect of economic knowledge on consumptive behavior, 4) knowing the effect of individual modernity on consumptive behavior. This research uses multiple linear regression method. The sample in this study were 110 students. Based on the results of the analysis it is known that there is an influence of financial literacy on consumptive behavior, there is an influence of economic knowledge on consumptive behavior, there is an influence of individual modernity on consumptive behavior and R2 value of 0.152 which means financial literacy, economic knowledge and individual modernity have an effect of 15.2% on Consumptive behavior of the 2014 Faculty of Economics and Business students. Thus the remaining 84.5% can be influenced by other factors that can be used as development material in further research.